Tax Revenue Effort and Aid in Fragile States : The Case of the Comoros - Diaz-Sanchez, Jose L.; Tagem, Abrams; Mota, Joana (World Bank, Washington, DC, 2021)
This paper assesses the impact of aid on tax revenue effort in the context of a fragile state, using the case of the Comoros. The paper estimates a fiscal response model within a cointegrated vector autoregressive framework with annual data for the Comoros’ post-independence period (1984-2017). The data suggest that grants and tax revenue in the Comoros had a significant negative relationship in the long run that remained stable throughout the post-independence period. Grants are a politically less costly source of finance, reducing the urgency of fragile states’ fiscal planners to expend their reduced political capital and administrative capacity on tax collection reforms. This effect may be amplified by the large one-off budget support grants, which represent a windfall of resources to the Comoros from bilateral partners, which often may have stopped tax reform initiatives. Although the paper does not suggest a decrease in aid to fragile states, as aid constitutes an essential support for these countries, being aware of this historically negative relationship is an important step to ensure that the government’s tax revenue efforts do not slow down following, for instance, large one-off unconditional budgetary support. In addition, the paper argues that prioritizing conditional aid, focusing on aid effectiveness, and engaging more resources for capacity-building tax revenue projects and technical assistance could increase the impact of donors’ interventions.